Bentuk Perlawanan terhadap Pembungkaman Kebebasan Berekspresi pada Akun Instagram @gejayanmemanggil - B. Arnold Simangunsong; Shenna (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2024)
The removal of the mural as a critical message in the Instagram account prompted a critical community @gejayanmemanggil to hold a Lomba Mural Dibungkam. The purpose of this article is to provide a vital explanation of the form of resistance that causes the act of silencing freedom of opinion as well as the disclosure of motives in constructing a message about resistance. The method uses Van Dijk's critical discourse model with text, social cognition, and context dimensions. The results found that the form of resistance was carried out directly, indirectly, and virtually through social media and made the message viral.